Clinical polymorphism in patients with Opisthorchis felineus infection in the Western Siberia. (2021) - Karbysheva, Nina; Nikonorova, Marina; Matros, Olga; Kiushkina, Irina; Nemilostiva, Elena; Choroshilova, Irina; Gorobchenko, Andrew; Umbetova, Karina; Volchkova, Elena
Highlights: Opisthorchiasis is the main helminthiasis of Western Siberia. The clinical picture of opisthorchiasis is non-specific. One of the key signs of opisthorchiasis is hypereosinophilia. Abstract: Clinical symptoms of chronic opisthorchiasis superinvasion the inhabitants of the Western Siberia, which is hyperendemic for this parasites, are presented. The polymorphism of manifestations from many organs and systems (liver, respiratory, immune, musculoskeletal, and digestive, etc.) with the development of eosinophilic hepatitis, according to histological studies, are shown. Manifestation of the latent course of the chronic phase of opisthorchiasis in case of repeated infection was accompanied by leukemoid eosinophilia, hyperleukocytosis and severe cholestasis, which determined the difficulties of the differential diagnostic search.